Analyzing the Policy of Work Safety and Health at State Polytechnic of Manado - Papia, Jedithjah Naapia Tamedi; Kesek, Meike Negawati (International Journal Labs, 2022)
Background: Many phenomena are found that policies, planning, and implementation of occupational safety and health (OSH) seem to have not been carried out to the fullest according to standards, so that some students, lecturers, administrative staff/technicians experience occupational safety and health problems. The purpose of OSH implementation is to guarantee the availability of a safe and healthy work environment for all people who work in the work environment. Aim: This study aims to find out, describe, and analyze OSH policy, OSH policy conformity with applicable regulations, and OSH policy commitments in the Manado State Polytechnic. Method: The research method used in this research is descriptive qualitative in order to obtain in-depth information about OSH policies. Data collection is obtained by: interview, observation, and documentation. By using the purposive sampling technique, researchers collect data from key informants. The number of key informants was 10 people, consisting of a managerial team who knew the OSH implementation process at the Manado State Polytechnic. Findings: The final result of this study is to be the basis for the implementation of the Occupational Safety and Health Management System (SMK3) in the Manado State Polytechnic is in accordance with the applicable rules and regulations.